2011
DOI: 10.1586/ern.11.153
|View full text |Cite
|
Sign up to set email alerts
|

The corticobasal syndrome–Alzheimer’s disease conundrum

Abstract: Corticobasal syndrome (CBS), once thought to be pathognomonic for corticobasal degeneration pathology, is increasingly reported with various underlying pathologies. Alzheimer’s disease is one such pathology, also once believed to be unique for its clinical syndrome of dementia of the Alzheimer’s type. CBS is believed to result from topography of asymmetric parietofrontal cortical lesion involvement, rather than lesion subtype. However, this topographical pattern is strikingly different to that typically associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 79 publications
0
44
1
Order By: Relevance
“…CBS-AD is thought to represent a form of earlyonset AD, but, at present, no genes have been identified 11 (in our cohort, APOE e4 status did not statistically differ between groups; nonetheless, the only 2 e4 homozygotes did belong to the CBS-AD group). Insofar as CBS-AD may represent a form of early-onset AD, it is consistent that one study found greater impairment of the dorsal stream in earlyonset AD than in late-onset AD.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…CBS-AD is thought to represent a form of earlyonset AD, but, at present, no genes have been identified 11 (in our cohort, APOE e4 status did not statistically differ between groups; nonetheless, the only 2 e4 homozygotes did belong to the CBS-AD group). Insofar as CBS-AD may represent a form of early-onset AD, it is consistent that one study found greater impairment of the dorsal stream in earlyonset AD than in late-onset AD.…”
Section: Resultscontrasting
confidence: 56%
“…5,11,13 The relatively young age of the patients with CBS-AD in this cohort would likely bias our result toward the null (if increasing age were causing an undetected spatial performance decline on the dorsal stream subtests). Furthermore, age-adjusted ORs were still significant for each spatial subtest.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the different phenotypes likely represent the distribution (eg, the brain areas affected) of the underlying pathology in each of these disorders, and thus, reflect more likely a spectrum rather than well-defined phenotypes, for which strictly defined clinical criteria can be applied. 10,39,45 Investigations MRI in CBD may show asymmetric frontoparietal atrophy. 46 DATscans are abnormal in CBD, as they are in PD, PSP, and MSA.…”
Section: The Phenotypic Spectrum Of Corticobasal Degenerationmentioning
confidence: 99%
“…CBS is an unusual clinical manifestation of various neurodegenerative pathologies, AD, FTD, corticobasal degeneration (CBD). The one related to AD presents a temporo-parietal atrophy prevalent on the left side and hypoperfusion of parietal lobe, with less involvement of pre-frontal regions compare with FTD and CBD [103].…”
Section: Progressive Apraxic Syndromementioning
confidence: 99%